2008
DOI: 10.1038/sj.ki.5002744
|View full text |Cite
|
Sign up to set email alerts
|

CD14++CD16+ monocytes but not total monocyte numbers predict cardiovascular events in dialysis patients

Abstract: Migration of monocytes into the vessel wall contributes to the onset and progression of atherosclerosis. Because monocytes are a heterogeneous population, we determined potential associations between monocyte subsets and cardiovascular events in a prospective cohort of 94 dialysis patients followed for 35 months. The incidence of cardiovascular events and death measured by Kaplan-Meier plots and flow cytometric analysis of monocyte subsets showed that total leukocyte and monocyte numbers failed to predict even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
181
3
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(198 citation statements)
references
References 37 publications
9
181
3
3
Order By: Relevance
“…This result was in accordance with recent studies [33][34][35] in patients on dialysis and with chronic kidney disease, which suggested an elevated risk of cardiovascular events when in the presence of a higher level of the intermediate monocytes. This finding also indicated that traditional risk factors accounted for only a small fraction of the excess risk.…”
Section: Discussionsupporting
confidence: 82%
“…This result was in accordance with recent studies [33][34][35] in patients on dialysis and with chronic kidney disease, which suggested an elevated risk of cardiovascular events when in the presence of a higher level of the intermediate monocytes. This finding also indicated that traditional risk factors accounted for only a small fraction of the excess risk.…”
Section: Discussionsupporting
confidence: 82%
“…Monocytes were gated in a SSC/CD86 ϩ dotplot identifying monocytes as CD86 ϩ cells with monocyte scatter properties. Subsets of Mo1, Mo2, and Mo3 monocytes were defined as reported earlier (11). Absolute numbers of monocyte subpopulations were calculated from the relative frequency among the monocytes as measured into the SSC/CD86 gate multiplied by the monocyte number determined by a differential cell count.…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…Both in vitro and animal studies suggested a selective role of distinct monocyte subpopulations in the development of atherosclerosis (15). In dialysis patients, Heine et al (16) showed that CD14 2ϩ CD16 ϩ monocytes but not total monocyte numbers predicted cardiovascular events. In that study, across increasing CRP and CD14 2ϩ CD16 ϩ monocyte tertiles, the death count became increasingly higher ( Figure 1A).…”
Section: Inflammatory Milieu Synergistically Stimulates Cytokine Prodmentioning
confidence: 99%